Do institutional investors drive the IPO valuation? - Chui, Zi Ong; Mohd Rashid, Rasidah; Taufil Mohd, Kamarun Nisham (Elsevier, 2020)
This study aimed to investigate the effect of institutional ownership on initial public offering (IPO) valuation and also to examine the indirect role played by the pricing mechanism on the relationship. Cross-sectional multiple regression was used to analyse the relationship between institutional ownership and IPO valuation based on the sample of 450 IPOs listed on Bursa Malaysia between January 2000 and December 2018. The results show that institutional ownership had a positive association with IPO valuation. The signalling role of institutional investors attempted to convey information on firms' qualities which in turn had approximately fair IPO valuations. Further, this study found that book-built IPOs with higher institutional ownership were priced more closely to the firms' intrinsic values. The results have implications for underwriters and issuers in signalling firms’ qualities through incorporating book-building in IPOs and allocating a higher number of shares to institutional investors.